THE CORONA PANDEMIC STORY : WHEN HOPE APPEARED ELUSIVE BY GEORGEMBURU - mburu, george (IJRDO - Journal of Social Science and Humanities Research, 2022)
The author undertakes a descriptive and synthesis and analysis of the novel Covid19 Pandemic dubbed as the Corona disease or the “Wuhan Virus”. Essentially, the author explores six objectives and points to the effects of the pandemic psychologically, health-wise, economically and even socially. Quint essentially, the author contends the untold value of prior planning in disaster preparedness and mitigation, a glaring challenge to all nations across the globe. Thirdly, the need for research as well as integrity and being resolute and for the right in the wake of disasters is being highlighted. The paper also highlights some statistical on the continuous rise and trends of the Covid19 which started in China in November 2019 spreading into all continents and most countries the world over. Towards the end vital lessons have been pointed out and recommendation made on the need form or research, impressing the need for the input of the key players and or stakeholders in response and mitigation of such a pandemic no wand in the future.